Eliminate the human factor. The automation of time determination at the Neuchâtel Observatory - Gressot, Julien (My University, 2021)
Throughout its existence, the Neuchâtel Observatory has sought to be at the forefront of astronomical time determination. In the mid-20th century, a technological innovation began to spread in observatories with PZTs (Photographic Zenith Tube). The Neuchâtel Observatory was one of the first to obtain this instrument, the purpose of which was to eliminate the human factor by automating the time determination and certain other instrumental errors. PZTs were presented as the most accurate instruments of their time, but their development was soon halted. In this paper, we will examine the technical evolution of PZTs, the reasons why they became the must-have instrument, and the explanations for their rapid abandonment.
, AHRC Observatory Networks – Workshop 1, Greenwich
Keywords: Neuchâtel Observatory; time determination; Scientific instruments; operating chain; cultures of precision; materiality